2018
DOI: 10.1177/1077559518808218
|View full text |Cite
|
Sign up to set email alerts
|

Higher Levels of Intelligence and Executive Functioning Protect Maltreated Children Against Adult Arrests: A Prospective Study

Abstract: Research shows that maltreated children are at elevated risk for arrest as adults and that higher verbal intelligence, reading ability, and executive functioning (abstract reasoning and cognitive flexibility) may be protective against criminal behavior. The current study examines this hypothesis using data from court substantiated cases of child abuse and neglect and demographically matched controls followed prospectively into middle adulthood (N = 1,196). At age 29, verbal intelligence was assessed with the Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 108 publications
(130 reference statements)
2
7
0
Order By: Relevance
“…Notably, 40% of individuals in this class reported involvement in higher education or vocational training. The pattern in this class is consistent with investigations that have found that positive educational experiences can be protective in buffering cascading effects for individuals with externalizing symptoms (Allwood & Widom, 2013; Nikulina & Widom, 2019; Smith, Park, Ireland, Elwyn, & Thornberry, 2013). Additionally, because emerging adulthood represents a period of peak substance use and the possible continuation of impulsivity and sensation-seeking that is common to adolescence (Masten et al, 2004), the high rates of externalizing behaviors and substance use in this class may simply reflect normative exploratory behaviors that have reached an apex, and will soon decline as individuals mature (Schulenberg et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Notably, 40% of individuals in this class reported involvement in higher education or vocational training. The pattern in this class is consistent with investigations that have found that positive educational experiences can be protective in buffering cascading effects for individuals with externalizing symptoms (Allwood & Widom, 2013; Nikulina & Widom, 2019; Smith, Park, Ireland, Elwyn, & Thornberry, 2013). Additionally, because emerging adulthood represents a period of peak substance use and the possible continuation of impulsivity and sensation-seeking that is common to adolescence (Masten et al, 2004), the high rates of externalizing behaviors and substance use in this class may simply reflect normative exploratory behaviors that have reached an apex, and will soon decline as individuals mature (Schulenberg et al, 2004).…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that IQ represents a set of core cognitive resources that protect against the negative effects of elevated conduct behaviors and substance use, allowing individuals in this group to do well in all other domains. This interpretation would be consistent with studies documenting the protective effects of IQ in resilient outcomes (Luthar & Zelazo, 2003; Masten et al, 1999; Masten et al, 2004; Nikulina & Widom, 2019). Alternatively, the increased externalizing problems in this class may represent environmentally adaptive behaviors that are conditional responses to disadvantaged contexts (Belsky, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These design characteristics represent major strengths, but they also pose limitations about the generalizability of the findings. 32 and reproduced in this paragraph with permission and minor modifications. Neglect cases reflected a judgment that the parents' deficiencies in childcare were beyond those found acceptable by community and professional standards at the time.…”
Section: Designmentioning
confidence: 99%